PELATIHAN PENGGUNAAN APLIKASI PENDETEKSI PALGIAT UNTUK DOSEN UNIVERSITAS LANCANG KUNING - Alexsander Yandra; Zamzami; Bayu Febriadi (Universitas Lancang Kuning, 2018)
University Lancang Kuning which is one of the leading educational institutions in Riau province, also produces superior products that are outstanding students and ready to face the world of sprinting and outstanding lecturers, as stated in the yellowish university mission